Eristic, Morality, and War - Szymanek, Krzysztof (Folia Philosophica, 2021)
The article addresses the ethical aspects of eristic and – more generally – the difficulties people encounter while evaluating debates in moral terms. Simplified and superficial ways to perceive eristical phenomena lead to inadequate assessments. Krzysztof Szymanek objects to the stereotype of eristic as the art of unfair debating and argues that eristical stratagems cannot be considered simpliciter as honest or dishonest without taking into account the circumstances under which arguments are exchanged. He gives and discusses examples of argumentative moves which, on the one hand, are deceptive, but, on the other, lead to the victory of what is right. A comparison of eristical fights to military battles helps to highlight the difficulties in formulating moral judgments about disputes.